Model Strategi Pengembangan Masyarakat Berbasis Desa Wisata di Situ Gunung Sukabumi - Fakhry Hafiyyan Kurniawan; Mahbub Afini Maulana (Lembaga Dakwah dan Pembangunan Masyarakat Universitas Cokroaminoto Yogyakarta (LDPM UCY), 2022)
Community development is an activity that is planned to improve the standard of living of the community through programs that are able to develop their potential and use local institutions as a forum for collective activities. Assessment of local aspects (including local institutions) in the community in the context of the community development process can explain the position of each local aspect in the community in achieving community development goals. systems approach using Soft System Methodology (SSM). Thus, it is expected to produce a conceptual model of the HR development strategy of the actors by increasing productivity in realizing prosperity and sustainability. The sample of this research is the Situ Gunung Tourism Village Community, Sukabumi Regency. The strategy of developing human resources (HR) and tourism in the object of this research is a strategic action to create competency and quality of human resources, develop local institutions, and empower communities.